ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK KACANG SANGRAI DI UD. AL-MURTADHA KABUPATEN PAMEKASAN - Rusli, Moh.; Sustiyana, Sustiyana; Nazizah, Fitrotin (Universitas Islam Madura, 2023)
Peanut (Arachis hypogaea) is an agricultural commodity that is needed by the community, bothas human food and industrial raw material. This study aims to determine consumercharacteristics, product quality of roasted peanuts, analyze consumer preferences for theattributes of roasted peanut products. The method used in this research is descriptive analysis.Based on the results of the research and analysis that has been carried out, it can beconcluded that roasted peanut products with the